Sistem Informasi Penerimaan Peserta Didik Baru Pada Pusat Pendidikan Komputer (PUSDIKOM) Muara Bungo - Finur, Hendra; Effiyaldi, Effiyaldi (Jurnal Manajemen Sistem Informasi, 2022)
The management of new student admissions at the Muara Bungo Computer Education Center (Pusdikom) is still conventional or manual, both in terms of managing registrant data and filling in registration forms. In the admin section, collect registration archives so that they are vulnerable to loss and problems in searching for prospective student data in changing registrant data. The purpose of this study was to analyze and design a new student admission information system at the Muara Bungo Computer Education Center (Pusdikom). The information system design method uses prototyping with system modeling tools, namely UML and interface design using Balsamiq Mockups 3.The output or results obtained from this study are the design of the information system for the admission of new students at the Muara Bungo Computer Education Center (Pusdikom) in terms of admin consisting of managing prospective new students, instructor data, department data, registration wave data, and category data management which will be displayed on the home page and from the leadership's point of view obtaining information about the number of registrants, the number of participants who took the selection exam, instructor & department info, as well as registration wave info. Meanwhile, prospective applicants get information about registration, including procedures, registration date, and test selection results and filling out the registration form. Suggestions that can be given are that further research can add other features and menus that are not made in this study and can make web-based and mobile applications.